Learning from failure of a long curved veneer wall : structural analysis and repair - Lourenço, Paulo B. (2013)
Masonry remains the most used material for enclosure and partition walls. Still, cracking often occurs in unreinforced masonry walls under service conditions and scarce information can be found about systemic approaches in real case studies. Here, attention is given to a large building faced with fired clay brick masonry veneer that exhibited significant out-of-plane movements only 1.5 years after construction. During the operation of dismounting part of the veneer, partial collapse occurred. The veneer wall, with an elliptical shape, 240 m length and 15 m height, presented no movement joints and insufficient tying. Irreversible expansion of the fired clay brick masonry was expected to be the main reason for damage. The combination of inspection works (visual inspection, pull-out tests and topographic survey) and advanced structural analysis with finite elements, allowed to understand the damage and propose a repair solution at a fraction of the cost of demolishing and rebuilding a and rebuilding a new veneer wall.